Acts of art and rebuttal in 1971 - Singerman, Howard 1953-; Watson, Sarah (Hunter College Art Galleries, 2018)
This exhibition revisits the 1971 exhibition "Rebuttal to the Whitney Museum Exhibition: Black Artists in Rebuttal", which was organized by members of the Black Emergency Cultural Coalition at Acts of Art, a small, artist-run gallery in Greenwich Village. The original exhibition was mounted in response to the Whitney Museum?s refusal to appoint a Black curator for their survey 'Contemporary Black Artists in America'. The exhibition at Hunter presents ten of the 47 artists from the original Rebuttal show, including Benny Andrews, Betty Blayton-Taylor, Vivian Browne, James Denmark, Cliff Joseph, Richard Mayhew, Dindga McCannon, Ademola Olugebefola, Haywood "Bill" Rivers, and Frank Wimberley. It is a selection intended to represent the stylistic diversity of the original exhibition, with works ranging from sardonic social satire and biting figurative expressionism to Yoruban-inspired symbolism and lyrical abstraction. Through these artists, the exhibition also traces a network of organizations and groups that supported the aspirations of Black artists and the community in the 1960s and early 1970s. Through its survey of the history of the short-lived Acts of Art gallery and the events leading up to the Rebuttalshow, the exhibition and its accompanying catalogue explore the intersections between Black cultural communities and cultural politics in Greenwich Village, the Lower East Side, and Harlem in the late 1960s and early 1970s.00Exhibition: Leubsdorf Gallery, New York, USA (04.10.-25.11.2018)
"Benny Andrews, Betty Blayton-Taylor, Vivian Browne, James Denmark, Cliff Joseph, Richard Mayhew, Dindga McCannon, Ademola Olugebefola, Haywood Bill Rivers, Frank Wimberley"--Back cover
Catalog of an exhibition at the Hunter College Art Galleries' Bertha and Karl Leubsdorf Gallery in the fall of 2018
Ausstellungsdaten ermittelt
"Edition of 400"--Colophon
Includes bibliographical references
Keywords: Geschichte 1971; Künstler; Person of Color; USA; Black Emergency Cultural Coalition; Rebuttal to the Whitney Museum Exhibition: Black Artists in Rebuttal (Exhibition) / (1971 / New York, N.Y.); African American art / 20th century / Exhibitions; African American artists / New York (State) / New York / History / 20th century / Exhibitions; Race awareness in art / Exhibitions; Art, American / 20th century / Exhibitions; African American art; African American artists; Art, American; Race awareness in art; History; Exhibition catalogs; New York (State); New York; Ausstellungskatalog -- Leubsdorf Gallery -- 04.10.2018-25.11.2018 -- New York, NY